Classy lip / Nur Zulaikha Zolkefli - Zolkefli, Nur Zulaikha (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
The goal of this study is to create a thorough makeover for Classy Lip, a home-based company that Siti Nur Hidayah Binti Mohd Yunus established in Seremban, Negeri Sembilan, on June 24, 2021. Classy Lip is a home-based company that specializes in creating handmade lip gloss items with an elegant and sophisticated look. The brand targets 18 to 35-year-olds who are fashion-conscious and wants to oﬀer a high-end lip gloss experience that matches their clients' sophisticated lifestyles. The stylish and simple logo design reﬂects the brand's emphasis on craftsmanship and attention to detail. The rose gold, soft pink, peach, and cream color scheme of Classy Lip's packaging screams luxury. The shade name and ingredients are listed on every lip gloss label, demonstrating the brand's dedication to using only natural, premium components. Classy Lip eﬀectively conveys its commitment to providing individualized and enjoyable customer experiences through its brand message. Additionally, in order to satisfy customers who care about the environment, the brand encourages eco-friendly packaging. One problem with the existing design is that there is no oﬃcial name for the product, which makes it less appealing because the logo doesn't have a visually appealing symbol or icon. "Where Elegance Meets Shine" is a memorable phrase that goes along with this logo. The idea behind the logo is to keep the original while enhancing it with Adobe Illustrator by adding element lips to make the logo more visually appealing. The print ads comprise of three categories: strawberry, peach, and vanilla. These advertisements will appear on billboards, outdoor posters, social media, subways, and bus stops. Digital designs encompass things like websites, exhibitions, and video advertising. In conclusion, the new Classy Lip logo will revitalize the business and draw in more clients or recognition.